Réseaux connectés d’enseignants et développement professionnel - Jacques Crinon; Georges Ferone (Recherches en Éducation)
Connected networks born from teacher initiatives have developed considerably in French-speaking countries in recent years. In particular they claim a dimension of co-training by peers. Based on interviews with teachers at the end of primary school and the beginning of secondary school practicing either the flipped classroom (n= 11) or the “twictée” (n= 19), we seek to know how, according to them, participation in a network of innovators contributes to their professional development. The study describes different types of participation in the network. It further indicates that reference knowledge is rarely at the center of discussions, rather centered on the educational organization, teaching tools and supports and the absence of professional controversies. We can thus see the incompleteness of the professional development process, if we stick to participation in the connected network, but also the need to consider this participation in a larger set of interactions and in development paths and personal networks where participation in a network can nevertheless play a decisive role at one point.